1999
DOI: 10.7863/jum.1999.18.10.673
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of gastric emptying by standardized real-time ultrasonography in healthy subjects and diabetic patients.

Abstract: The aim of this study was to simplify and standardize a reproducible, well-tolerated and clinically applicable method for the assessment of gastric emptying rate by real-time ultrasonography. A total of 33 subjects were examined, including 19 healthy subjects and 14 patients with insulin-dependent diabetes mellitus and clinically suspected delayed gastric emptying. Measurements of the gastric antrum were taken in the supine position and in relation to internal landmarks to obtain a standardized cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
113
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(118 citation statements)
references
References 41 publications
4
113
0
1
Order By: Relevance
“…The mean value of GER in the Emirati diabetic patients was estimated to be 17%, which is less than half the rate in the healthy volunteers (50%), (p < 0.001). In a study on Swedish diabetic patients, using the same standardized ultrasound method for gastric assessment [19], the median GER was higher (29%) than the one reported in this study (17%), even though the Swedish patients were selected for clinically suspected gastroparesis. This could be explained by differences in caloric content of the test meals since the rate of gastric emptying is a function of the caloric density of the ingested meal [21]- [23].…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…The mean value of GER in the Emirati diabetic patients was estimated to be 17%, which is less than half the rate in the healthy volunteers (50%), (p < 0.001). In a study on Swedish diabetic patients, using the same standardized ultrasound method for gastric assessment [19], the median GER was higher (29%) than the one reported in this study (17%), even though the Swedish patients were selected for clinically suspected gastroparesis. This could be explained by differences in caloric content of the test meals since the rate of gastric emptying is a function of the caloric density of the ingested meal [21]- [23].…”
Section: Discussionmentioning
confidence: 60%
“…However, studies have shown that this reduction is not large enough to be relevant [32]. Some studies have shown a difference between females and males regarding gastric emptying [33] [34] while others did not find any difference [19]. Obesity seems to be related to lower GLP levels and increased gastric emptying [35]- [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasonography examination indirectly determines gastric emptying by real-time evaluation of changes in the antral area. Further studies showed that the values obtained with real-time ultrasonography did not differ grossly from those obtained with scintigraphy (15,16). In this study, our results showed that real-time ultrasonography significantly correlated with the clinical symptom scores of FD, and could be used as an objective method for the evaluation of FD.…”
Section: Discussionmentioning
confidence: 99%
“…Research studies have shown an overall delayed rate of gastric emptying in functional dyspepsia, with occasional, more rapid initial emptying (Lunding et al, 2006) and an overall delayed rate of gastric emptying in patients with longstanding type 1 (Darwiche et al, 1999) and type 2 (Bian et al, 2011) diabetes. …”
Section: D Assessment Of Gastric Emptyingmentioning
confidence: 99%